AIDS The Global Impact. Academy for Educational Development 25th Anniversary Seminar Series - Mann, Jonathan; Academy for Educational Development, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This paper describes why acquired immune deficiency syndrome (AIDS) is a global health problem and discusses special features of the virus and its infection. This disease's transmission and interaction with other diseases, along with 1986 statistics concerning AIDS, are presented in terms of selected continents and countries. The World Health Organization's (WHO) role in helping other countries develop their own educational materials and strategies for handling the disease are highlighted, along with this organization's efforts to provide technical and financial support to individual countries so that they are able to undertake national AIDS prevention programs. A question and answer section is included. (JHP)
Availability: Academy for Educational Development, 1255 23rd St., NW, Washington, DC 20037.
ERIC Note: Based on a speech presented as part of the Academy for Educational Development's 25th Anniversary Seminar Series (Washington, DC, December 1986).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Acquired Immune Deficiency Syndrome; Communicable Diseases; Disease Control; Disease Incidence; Global Approach; Health Programs; Position Papers; Public Health; Impact -- World Health Organization; Speeches/Meeting Papers; Reports, Descriptive; Opinion Papers